Long-Term Outcomes of Prostate Capsule-Sparing and Nerve-Sparing Radical Cystectomy With Neobladder: A Propensity Score-Matched Comparison - Zhu, Zaisheng; Zhu, Yiyi; Shi, Hongqi; Zhou, Penfei; Xue, Yadong; Hu, Shengye (International neurourology journal, 2024)
Purpose: This study aimed to compare and analyze the feasibility and long-term efficacy of prostatic capsule-sparing (PCS) and nerve-sparing (NS) radical cystectomy in the treatment of bladder cancer.Methods: From June 2004 to December 2021, our institution treated and followed 145 patients who underwent radical cystectomy with neobladder reconstruction for over a year. These patients were divided into 2 groups: PCS (n=74) and NS (n=71). To minimize potential biases, 1:1 propensity score matching was utilized to compare oncological outcomes, functional outcomes, and complications between the groups. Additionally, Kaplan-Meier analysis and the log-rank test were used to evaluate survival differences between the PCS and NS groups.Results: The median follow-up durations for PCS and NS were 155 and 122 months, respectively. After adjusting for propensity scores, a total of 96 patients (48 in each group) were included for further analysis. Kaplan-Meier curves showed no statistically significant differences in metastasis-free probability (P=0.206), cancer-specific survival (P=0.091), and overall survival (P=0.208). The daytime urinary control (UC) rate at 3, 6, and 12 months postoperatively was 72.9%, 91.7%, and 97.9% in the PCS group and 47.9%, 79.2%, and 91.7% in the NS group, respectively (P=0.012, P=0.083, and P=0.362). The nocturnal UC rate was 54.2%, 85.4%, and 95.8% in the PCS group, and 31.3%, 60.4%, and 83.3% in the NS group, respectively (P=0.023, P=0.006, and P=0.091). Regarding erectile function recovery, 62.5% of patients in the PCS group and 22.9% in the NS group returned to preoperative levels (P<0.001).Conclusions: PCS outperformed NS in restoring UC and sexual function and did not affect oncological outcomes. However, PCS was associated with a higher risk of complications linked to bladder-neck obstruction.